Bio-psycho-social predictors of physical disability and depression among meat-packing workers attending an occupational rehabilitation program - Sardá Junior, Jamir João; Kupek, Emil; Cruz, Roberto Moraes (Acta Fisiátrica, 2009)
A large number of workers are afflicted by occupational diseases that have chronic pain, disability, and depression among their symptoms. Although there is evidence on contributory factors related to the working environment as well as physical factors involved in occupational diseases, disability and depression associated with these conditions are multidimensional phenomena mediated by bio-psycho-social aspects. This paper examines the relationships between clinical, environmental, and demographics factors, and disability and depression in a sample of workers from the meatpacking industry (n=234) attended by an occupational rehabilitation program. This study can be described as cross-sectional, and uses descriptive and inferential statistics (multivariate regressions). Data was collected using a demographic and clinical questionnaire, the Roland-Morris Questionnaire, the HADS depression scale, and the Measure of Functional Independence (MFI). The results show that, by all measurements used, the final score (post-rehab.) was strongly determined by the initial score (pre-rehab.) with little influence from other independent variables. Changes in the levels of disability appeared to be associated with financial gain (p=0.057). The final score on the MFI was inversely related to the time off work (p=0.006). Variations among the final scores of the CID-10 categories were not conclusive. On the whole there was a preponderance of women among those on sick leave, also with high incidence of musculoskeletal disorders and depression or both. The age variable was the predictor for RM disability, whereas time off work was the predictor for disability by MFI. None of the variables analyzed affected the depression scores. Generally these results are consistent with those found in the literature and confirm that diverse factors contribute to the disability and depression of workers with occupational diseases, as predicted by the bio-psycho-social model.